Large exchange bias effect in the super spin glass state of Mn50Ni38Al12 alloy. (July 2017) - Pan, H.; Ma, L.; Li, G.K.; Jia, L.Y.; Zhen, C.M.; Hou, D.L.; Wang, W.H.; Liu, E.K.; Chen, J.L.; Wu, G.H.
Abstract: A large exchange bias field ( H EB ) of 5.3 kOe which so far, is the largest value found in MnNi-based alloys, was observed in Mn50 Ni38 Al12 ribbon. DC and AC magnetic measurements show super spin glass (SSG) behavior below 130 K and superparamagnetic behavior above this temperature. Different from other systems, the pinning and pinned phases are both SSG. Due to the high content of Mn and low content of Al there exists considerable disorder in Mn50 Ni38 Al12 which is responsible for the large H EB . Highlights: A large exchange bias field of 5.3 kOe has been observed in Mn50 Ni38 Al12 polycrystalline ribbon. The pinning and pinned phases are both SSG for Mn50 Ni38 Al12 . There possesses a temperature-induced dynamic transformation between them. It is found that there exists considerable antisite disorder in Mn50 Ni38 Al12 which is responsible for the large H EB .